A Novel Poly(ε-Caprolactone)-Based Photo-Crosslinkable Liquid Copolymer as a Versatile Drug Delivery Platform - Marcus Flowers; Nicole Mertens; Amanda Billups; Brenda M. Ogle; Chun Wang (MDPI AG, 2024)
Background/Objectives: Hydrophobic semi-solid or liquid biodegradable polymers have shown unique advantages as injectable matrices for sustained release of a wide range of drugs. Here we report the design, synthesis, and characterization of a new low-melt liquid copolymer based on poly(ε-caprolactone) (PCL) and establish its utility as a versatile delivery platform. Methods: The copolymer, mPA20, consisting of short PCL blocks connected via acid-labile acetal linkages, was synthesized using a one-pot reaction and its properties were comprehensively characterized. Results: mPA20 is an amorphous, injectable liquid at physiological temperature and can undergo pH-sensitive hydrolytic degradation. mPA20 bearing methacrylate end groups can be photo-crosslinked into solid matrices with tunable mechanical properties. A hydrophobic fluorophore, Nile Red (NR), was solubilized in mPA20 without any solvent. Sustained release of NR into aqueous medium was achieved using mPA20, either as an injectable liquid depot or a photo-crosslinked solid matrix. Further, mPA20 self-emulsified in water to form nanodroplets, which were subsequently photo-crosslinked into nanogels. Both the nanodroplets and nanogels mediated efficient intracellular delivery of NR with no cytotoxicity. Conclusions: mPA20, a new photo-crosslinkable, hydrophobic liquid copolymer with pH-sensitive degradability, is highly adaptable as either an injectable or implantable depot or nanoscale carrier for the controlled release and intracellular delivery of poorly soluble drugs.